Bioavailability of legacy and current-use pesticides in juvenile Chinook salmon habitat of the Sacramento River watershed: Importance of sediment characteristics and extraction techniques. (July 2022) - Fuller, Neil; Anzalone, Sara E.; Huff Hartz, Kara E.; Whitledge, Gregory W.; Acuña, Shawn; Magnuson, Jason T.; Schlenk, Daniel; Lydy, Michael J.
Abstract: The Sacramento River watershed, California, provides important rearing and migratory habitat for several species of conservation concern. Studies have suggested significant benefits for juvenile fish rearing in floodplain habitats of the watershed compared to the mainstem Sacramento River. However, the potential for contaminant exposure in each of these two habitats is poorly understood. Consequently, the present study aimed to determine the distribution and occurrence of bioavailable pesticides within two known salmon habitats using a suite of approaches including exhaustive chemical extraction, single-point Tenax extraction (SPTE) and ex situ passive sampling. Sediment samples were collected from sites within both habitats twice annually in 2019 and 2020, with inundation of the floodplain and high flows for both areas in 2019 and low flow conditions observed in 2020. Sediment characteristics including total organic carbon, black carbon and particle size distribution were determined to elucidate the influence of physical characteristics on pesticide distribution. Using exhaustive extractions, significantly greater sediment concentrations of organochlorines were observed in the floodplain compared to the Sacramento River in both years, with bioaccessible organochlorine concentrations also significantly greater in the floodplain (ANOVA, p < 0.05). Using both SPTEs and exhaustive extractions, significantly fewer pesticides were detected across both sites under low flow conditions as compared to high flow conditions (Poisson regression, p < 0.05). Sediment characteristics including percent fines and black carbon had significant positive relationships with total and bioaccessible pyrethroid and organochlorine concentrations. Fewer analytes were detected using low-density polyethylene (LDPE) passive samplers as compared to SPTEs, suggesting greater sensitivity of the Tenax technique for bioavailability assessments. These findings suggest that threatened juvenile fish populations rearing on the floodplain may have greater exposure to organochlorines than fish inhabiting adjacent riverine habitats, and that pesticide exposure of resident biota may be exacerbated during high-flow conditions. Graphical abstract: Image 1 Highlights: Pesticide presence and bioaccessibility assessed in two important salmon habitats. Ex situ passive sampling, exhaustive and single-point Tenax extractions used. Higher organochlorine concentrations in floodplain compared to riverine habitats. Fewer total and bioaccessible pesticides detected during low flow conditions. Organochlorine and pyrethroid concentrations related to black carbon and % fines.